Impact of the herbal medicine, Ephedra sinica stapf, on gut microbiota and body weight in a diet-induced obesity model - Song, Eun-Ji; Shin, Na Rae; Jeon, Songhee; Nam, Young-Do; Kim, Hojun (Frontiers in Pharmacology, 2022)
Obesity is a chronic metabolic disease caused by excessive body fat and has become a global public health problem. Evidence suggests that obesity and obesity-induced metabolic disorders are closely related to gut microbiota. Bupropion (BP), an antidepressant medicine, and Ephedra sinica (ES), a herbal medicine, are sympathetic stimulants and have weight loss effects. However, no studies have simultaneously assessed the effects of drugs and herbal medicines on obesity and gut microbiota. This study aimed to determine the effects of BP and ES on weight loss and re-modulation of host gut microbiota. We hypothesized that BP and ES exert anti-obesity effects by regulating gut microbiota and, consequently, reducing the accumulation of fat storage. Weight loss was confirmed in both BP and ES; however, it was more pronounced in ES. We investigated the composition of gut microbiota and explored its correlation with fat accumulation. ES changed the overall composition of the gut microbiota by restoring the relative abundance of Oscillospiraceae, Lachnospiraceae, and the Firmicutes/Bacteroidetes ratio, an indicator of gut microbiota dysbiosis. There were some changes in the gut microbiota due to BP; however, these were not as distinct as ES. Nine amplicon sequence variants (ASVs) of the gut microbiome were significantly recovered by BP and ES treatment, of which eight ASVs correlated with body weight and fat accumulation. Additionally, three ASVs were significantly recovered by ES treatment alone. In conclusion, the anti-obesity effects of BP and ES, especially fat accumulation, are related to the regulation of gut microbiota. Moreover, ES had a greater influence on the gut microbiota than BP.